Segregation of bunch orientation in plantain and banana hybrids - Ortíz, R.; Vuylsteke, D.R. (1998)
Bunch orientation is an economically important trait in plantain ( Musa spp. AAB group) and banana ( Musa spp. AAA or ABB groups). Pendulous bunches are more symmetrical than subhorizontal, horizontal, or erect bunches and are, therefore, better adapted for transportation. Erect, horizontal, subhorizontal, and pendulous bunches were observed in segregating opulations derived from crosses between plantains and bananas and among bananas. A proposed genetic model controlling this trait was tested in four populations. The true breeding diploid banana line, 'Calcutta 4' shows a pendulous bunch and has recessive alleles at three bunch orientation loci. The diploid banana cultivar 'Pisang lilin', which is heterozygous for the three loci, has a subhorizontal bunch. The triploid AAB plantain cultivar 'Bobby Tannap' has two simplex and one duplex loci, which also results in subhorizontal bunch orientation. The other plantain cultivar, 'Obino l'Ewai', which is simplex for two loci and nulliplex for the third, has a pendulous bunch due to dosage effects at the triploid level of the recessive alleles at simplex loci. Two tetraploid hybrids (TMPx 582-4 and 1187-8) have a subhorizontal bunch because of its uplex genotype for two loci and simplex genotype for the other locus. Bunch orientation might be an oligogenic trait regulated by the epistatic effects of at least three dominant loci.